Using computational models to understand CO2-rich fluid behaviour, photochemical reactions and high-temperature water reactions. - Wiseall, Christopher (2020)
This Thesis uses computational model development throughout to aid with the understanding of experimental results in two general areas: understanding phase behaviour of CO2-rich fluids and modelling of novel chemical reactions.